2010
DOI: 10.1002/mame.200900292
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Cryogel Cross‐Linked by Dialdehyde Starch

Abstract: A 3D spongy collagen cryogel was prepared using DAS as the cross‐linker. FTIR and CD studies demonstrate that crosslinking is achieved through the reaction of the DAS aldehyde groups with the free amino groups in collagen without affecting the triple helix of collagen. SEM demonstrates that the cryogel has a heteroporous structure with interconnecting pores. DSC measurements reveal that the cryogels have improved thermal stability in comparison with pure collagen. Moreover, the ESR shows that the water uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 43 publications
4
80
0
1
Order By: Relevance
“…EDC cross-linked collagens show reduced calcification, with no cytotoxicity and slow enzymatic degradation (Khor, 1997;Pieper et al, 1999). Some natural non-toxic and biodegradable molecules with favourable biocompatibility have been exploited as protein cross-linkers, such as D,L-glycceraldehyde (Sisson et al, 2009), oxidized alginate (Balakrishnan & Jayakrishnan, 2005), dialdehyde starch (DAS (Mu et al, 2010), Fig. 10) and genipin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…EDC cross-linked collagens show reduced calcification, with no cytotoxicity and slow enzymatic degradation (Khor, 1997;Pieper et al, 1999). Some natural non-toxic and biodegradable molecules with favourable biocompatibility have been exploited as protein cross-linkers, such as D,L-glycceraldehyde (Sisson et al, 2009), oxidized alginate (Balakrishnan & Jayakrishnan, 2005), dialdehyde starch (DAS (Mu et al, 2010), Fig. 10) and genipin.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, cross-linking permits a reduction in the antigenicity of collagen and, in some forms, decreases its calcification (Damnik, 1996). Charulatha et al, 2003;Kikuchi et al, 2004;Mu et al, 2010Mu et al, 20102003, Friess;1999, Khor, 19972001 Park et al;2002, Pieper et al;1999, Kim et al, 2001, Song et al, 2006Friess, 1999Friess, 1999Khor, 1997Jackson et al, 2010 Ko et al;Yan et al, 2010 Sisson et al;2009, Farrist et al;Martucci & Ruseckaite, 20092010, Natu et al;2007, Chang et al;2007, Kuijpers et al;2000 Vargas et al;2008 Kim et al;Pena et al;2010 Yao et al;2005, Lien et al;, Bigi et al, 2002Chiono et al, 2008;Mi et Table 1). …”
Section: Cross-linking Of Collagen Vs Gelatine and Their Immuno Respmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, dialdehyde polysaccharides prepared after periodate oxidation appeared to be an attractive option for stabilization of protein via Schiff base reaction as it is abundant and one of the cheapest and eco-acceptable raw material and this process was an automatic reaction which could get rid of the dependence on other crosslinking agent. The efficiency of dialdehyde starch (DAS) as crosslinking agent of solution-casting films based on gelatin (Martucci and Ruseckaite 2009), collagen (Mu et al 2010), egg-white protein (Gennadios et al 1998) has been documented. Dialdehyde cellulose (DAC) was utilized to immobilize collagen according to the study of Kanth et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some reports have demonstrated that PDMAEMA can act as both reducing agent and stabilizer simultaneously in the formation of gold nanoparticles, [21][22][23][24] based on the fact that Poly (2-(dimethylamino) ethyl methacrylate) (PDMAEMA) is a hydrophilic polymer with temperature and pH sensitivities, excellent biocompatibility, and a well-studied environmentally responsive polymer. 25 Such an approach greatly simplified the preparation and purification of gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%